Noise and vibration analysis : signal analysis and experimental procedures - Brandt, Anders (Chichester, West Sussex, U.K. ; Wiley, 2011)
'Noise and Vibration Analysis adopts a practical learning approach, building upon two existing class-note type books that have been used by the author for 10 years of teaching two academic courses'--
Includes bibliographical references and index.
Keywords: Vibration -- Mathematical models; Noise -- Mathematical models; Acoustical engineering; Stochastic analysis; Signal processing; TECHNOLOGY & ENGINEERING / Drafting & Mechanical Drawing